Tomato and pepper grafting for high tunnel production: effects on yield, compatibility, and plant morphology - Loewen, David (Kansas State University, 2018)
Tomatoes and peppers are the most popular and profitable high tunnel crops. However, year-round intensive cultivation and extensive monocropping can lead to a loss of soil quality and the buildup of soilborne pathogens. Many growers are considering grafting to help address the drawbacks of covered agriculture and improve yields. Although many trials have been conducted that examine the ability of rootstock to increase yield or reduce disease, the effect of scion cultivar has yet to be tested, and few studies have attempted to quantitatively assess scion compatibility. In 2016 and 2017, we evaluated ten hybrid, determinate, red slicing tomato scion cultivars for compatibility with ‘Maxifort’ rootstock in a three-season high tunnel in Olathe, KS. While all ten varieties were compatible with ‘Maxifort’, only ‘BHN 589’, ‘Red Deuce’, ‘Skyway’, and ‘Tasti Lee’ were “highly compatible” and showed significant improvements in marketable yield when grafted. Additionally, when ranked by yield, differences between grafted and nongrafted populations suggest that relative compatibility may be inconsistent between varieties. However, a significant inverse relationship between the yield of the nongrafted plants and the percent yield benefit from grafting indicates that the effect of a rootstock like ‘Maxifort’ may not be synergistic, with higher performing nongrafted scion varieties benefitting less from grafting than lower performing varieties. ‘Red Deuce’ and ‘BHN 589’ are productive, and highly compatible grafted varieties with potential for commercial high tunnel production. ‘Primo Red’ benefitted the least from grafting but was the highest performing nongrafted variety (outperforming four of the grafted combinations). Compared to tomatoes, published reports on grafted peppers have been limited and it is unclear whether they provide any advantage in the absence of soilborne disease or environmental stress. Additionally, the use of rootstocks from other solanaceous species outside the Capsicum genus for pepper grafting has not been well explored, though the pool of available rootstock options for peppers would be substantially increased if such graft unions proved to be compatible. The goals of a second project were to identify the utility of grafted pepper (C. annum) plants for commercial high-tunnel production and to explore the potential for graft compatibility between the Capsicum and Solanum genera. We grafted ‘Karisma’ bell peppers onto two Solanum cultivars (‘Maxifort’ and ‘Sweetie’) and three pepper rootstocks (‘Scarface’, ‘Meeting’, and ‘Yaocali’). Five trials were conducted in 2016-2017 and utilized a randomized complete block design in all locations. Plants grafted onto Solanum rootstocks displayed symptoms of delayed incompatibility, including significant (78%-89%) reductions in yield (by weight), 59%-93% less plant growth, and 58% less marketability, as well as malformations at the graft union and higher in-field mortality rates. These symptoms were likely due to differences in mature stem anatomy. Plants grafted to ‘Scarface’ produced 32% greater marketable yield, 15%-18% larger fruit, and 9-12% higher marketability than nongrafted ‘Karisma’. The results for ‘Yaocali’ were similar to ‘Scarface’, though less conclusive. While ‘Yaocali’ and ‘Scarface’ rootstocks may be useful for improving yield in low-stress environments, the use of ‘Meeting’ may be more beneficial for combatting disease.
Keywords: Tomato; Pepper; High tunnel; Intergeneric; Grafting; Compatibility